Real Time Application of Fourier Transforms - S. S.Shenbaga Ezhil (Institute of Advanced Engineering and Science, 2017)
In recent days increasing the use of Fourier transform in various applications. The Fourier transform is the simplest among the other transformation method. It is less time consuming, used in power distribution system, mechanical system, industry and wireless network. Mainly in power distribution system the mitigation of power quality disturbance require fast, accuracy and high noise immune method. In the Fourier Transform (FT) area, the advancements of oversampling, computerized sifting and clamor molding are generally received for smothering the quantization commotion. The powerful quantize bits of an ADC are enhanced in view of these techniques. In any case, when preparing the wideband signs for example, linear frequency modulation flag, these strategies can't get viable results, and need high testing rate.